Usefulness of Platelet Function Tests to Predict Bleeding With Antithrombotic Medications. Issue 6 (November 2015) - Gorog, Diana A.; Otsui, Kazunori; Inoue, Nobutaka
Abstract : The pharmacological inhibition of platelets has always been regarded as a double-edged sword: the challenge of balancing the antithrombotic effect against the bleeding risk. Potent antiplatelet agents and novel oral anticoagulants, sometimes in combination, are increasingly used in the treatment of cardiovascular disease and for thromboprophylaxis in atrial fibrillation. Although such treatment has reduced the risk of thrombotic events, the potential for major bleeding has increased, and a technique to identify those at increased bleeding risk is greatly needed. Platelet function tests (PFTs), most frequently VerifyNow and also the vasodilator-stimulated phosphoprotein -phosphorylation assay, have been used to identify low on-treatment platelet reactivity, to identify individuals who may be at increased bleeding risk. Such results predict nuisance bleeding, but many individuals have low on-treatment platelet reactivity and yet do not exhibit major or even minor bleeding. Although PFTs may be useful in assessing populations, they do not allow identification of individual patients at risk of bleeding on either antiplatelet or novel oral anticoagulant therapy, nor do they allow the tailoring of such therapy to optimize the risk:benefit ratio. Thrombin plays a cardinal role in both arterial thrombus formation and hemostasis, yet most PFTs fail to assess the contribution of thrombin, because they employ anticoagulated blood. Techniques such as the calibrated automated thrombogram and the point-of-care global thrombosis test, performed on native blood, which measure endogenous thrombin potential, seem to show the most promise for profiling bleeding risk, as tests that most physiologically assess the effects of medications on thrombin.